Enhancement of heat transfer performance of water using nanoparticles - Amran N.A.M.; Mohamed H.; Gunnasegaran P.; Satgunam M.; Ismail I.N.; Roslan E. (American Institute of Physics Inc., 2023)
The purposes of this study are to investigate the thermal conductivity and the specific heat capacity improvement of water using SiC nanoparticles and also to evaluate the effects on heat transfer performance when using two different mass concentrations of SiC powder and heating powers that range from 20 W to 60 W. The experiment is carried out using a Loop Heat Pipe (LHP) experimental setup. The size of SiC nanoparticles used is approximately 169 nm. The results show that the thermal conductivity and the specific heat capacity of the nanofluid are slightly higher than those of distilled water at a same heat input. For a given heat input, the thermal conductivity is found to increase with the addition of the SiC nanoparticle mass concentration. The thermal conductivity also depends on the heat input. For 0.3% SiC mass concentration the thermal conductivity is improved up by 10.5%, 19.7% 56.6% at 20 W, 40 W and 60 W, respectively. For 1.0% mass concentration, the conductivity has improved by 16.2%, 20.7% and 64.9% at heating powers of 20 W, 40 W and 60 W. The specific heat capacity is also improved when the mass concentration of SiC is increased, improving it from 0.95 J/kgK (distilled water) to 3.89 J/kgK (0.3% SiC) and 3.91 J/kgK (1.0% SiC). 2018 Author(s).